INVESTIGATING THE COMPONENTS OF OUTCOME BASED EDUCATION IN EFL CLASSROOM: A LESSON PLAN ANALYSIS - Nurti Rahayu; Dwi Sloria Suharti; Fikri Asih Wigati; Emi Taufanawati (University of Kuningan, 2021)
This study aimed to investigate the implementation of Outcome-Based Education (OBE) to teach English in a vocational school. This study is qualitative with document analysis. The data were taken from four-session English lesson plans from a vocational school, observation, interview, and library research. The results showed the crucial impact of OBE to ensure the learning outcome, especially in a vocational school. OBE is expected to answer the education challenge in the 21st century to provide students with the required skills and competency. The area of analysis covers three areas: objectives, teaching materials, and assessment. It is recommended that teachers construct concrete materials and action in the viewpoint that the English skills taught can be used in the students' lives in the upcoming time in their future job related to the expertise in accounting. Finally, this study has important implications for accomplishing the framework for the practice and methods of goal setting, classroom activities, and assessment and evaluation of student's performance based on the OBE framework.